(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2005)
The results of investigation of biomorfological and economically valuable characteristics of six species of genus Origanum L. in conditions of a Southern coast of Crimea are summed up. High-productive forms have been recommended to cultivation in the south of Ukraine and apply in food industry and in medicine.